Pendidikan Urgensi Menurut Al-Qur’an Dan Hadis - Abdul Qodir; Abdus Somad; Abdurrahman Abdurrahman (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This article discusses the importance of education in the view of the Qur'an and Hadith using a literature study method, which involves searching various sources such as tafsir books, hadith, and Islamic books. From the results of the study, it is known that education in Islam occupies a very important position, because it is the main way for humans to know Allah, develop their intellect, and form good character. The Qur'an provides the basis for educational teachings, for example through Surah Al-'Alaq [96]: 1-5, which commands us to read and learn, and Surah Al-Mujādilah [58]: 11, which explains that Allah raises the status of those who have knowledge. Meanwhile, the hadith of the Prophet ﷺ emphasizes the obligation to seek knowledge and explains its great importance for every Muslim. Exegetes such as Al-Jalalain, Al-Qurṭubi, Ibn Kathir, and Wahbah az-Zuhaili explain that education is not only about increasing knowledge, but also about drawing closer to Allah and improving morals. Therefore, the values of education in the Qur'an and Hadith need to be revived in today's education system in order to produce a generation that is intelligent, faithful, and of noble character.